Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1002/jcp.24085
|View full text |Cite
|
Sign up to set email alerts
|

Protein sequences involved in the mitochondrial import of the 3,5,3′‐L‐triiodothyronine receptor p43

Abstract: The major effect of T3 on mitochondrial activity has been partly explained by the discovery of p43, a T3-dependent transcription factor of the mitochondrial genome. P43 is imported into mitochondria in an atypical manner which is not yet fully understood. Our aim was to characterize the p43 sequences inducing its mitochondrial import, using in organello import experiments with wild-type or mutated proteins and validation in CV1 cells. We find that several sequences define the mitochondrial addressing. Two alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Studies in diverse cells types, including human adipose-derived stem cells (hADSC), human primary osteoblasts, mouse osteoblast-like MC3T3 cells, monkey kidney cells (CV-1), neonatal rat ventricular myocytes (NRVM), and mouse cardiomyocytes (HL-1), have revealed TR subtypes localized to the mitochondria, plasma membrane, and cytoplasmic compartments in a tissue-specific manner (Carazo, et al 2012; Cvoro et al 2016; Kalyanaraman et al 2014; Wadosky, et al 2016). Of particular interest, human ADSCs are multipotent adult stem cells with the capacity to differentiate into adipocytes, chondrocytes, and osteocytes, and they express TRα1, TRα2, and TRβ1 at variable levels.…”
Section: Cytoplasmic Functions Of the Thyroid Hormone Receptormentioning
confidence: 99%
“…Studies in diverse cells types, including human adipose-derived stem cells (hADSC), human primary osteoblasts, mouse osteoblast-like MC3T3 cells, monkey kidney cells (CV-1), neonatal rat ventricular myocytes (NRVM), and mouse cardiomyocytes (HL-1), have revealed TR subtypes localized to the mitochondria, plasma membrane, and cytoplasmic compartments in a tissue-specific manner (Carazo, et al 2012; Cvoro et al 2016; Kalyanaraman et al 2014; Wadosky, et al 2016). Of particular interest, human ADSCs are multipotent adult stem cells with the capacity to differentiate into adipocytes, chondrocytes, and osteocytes, and they express TRα1, TRα2, and TRβ1 at variable levels.…”
Section: Cytoplasmic Functions Of the Thyroid Hormone Receptormentioning
confidence: 99%
“…Subsequently, Casas and colleagues [ 53 ] demonstrated that p43 is indeed restricted to the mitochondria, and that it has similar ligand binding affinity to TRα1, indicating that p43 is the receptor which drives TH mediated transcription of the mitochondrial genome [ 54 , 55 ]. p43 translocates into the mitochondria via fusion to a cytosolic protein [ 56 ], and once within the mitochondrial matrix, TH binding to p43 results in p43 interaction with the mitochondrial genome via TREs located in the D loop of the heavy strand [ 6 ] to initiate transcription. This mechanism explains the observation of an increased mRNA/rRNA ratio within the mitochondria after exposure to TH [ 57 ].…”
Section: Indirect Effectsmentioning
confidence: 99%
“…Soluble factor dependence, chilling inhibition, and energy dependence are commonly used criteria when establishing a signal-mediated import pathway (Carazo et al, 2012; Dhanoya et al, 2013; Umemoto and Fujiki, 2012; Vazquez-Iglesias et al, 2009, 2012), and thus demonstrate a requirement for signal-mediated nuclear import of TRα1 in HeLa cells. To begin to characterize the soluble components required for nuclear localization of TRα1, we turned to an in vivo approach to evaluate the role of a panel of importins in promoting TRα1 nuclear import in HeLa cells.…”
Section: Resultsmentioning
confidence: 99%